2009
DOI: 10.1111/j.1439-0272.1995.tb01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Male reproductive potential after MOPP therapy for Hodgkin's disease: a long-term survey

Abstract: The testicular function of 47 men who had been treated by MOPP chemotherapy for a Hodgkin's disease was studied in a long-term survey. Azoospermia was constant during at least 14 months after completion of the treatment. After a follow-up period of 89.4f54.7 months, 26 men were still azoospermic. No correlation could be found between the therapeutic regimen and the results of semen analysis. For the same treatment, some men recovered spermatogenesis within 5 years, others after more than 10 years while some we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…For instance, a return to normozoospermic levels was observed in 70% of men who received cumulative doses of cyclophosphamide under 7.5 g/m 2 , whereas only 10% recovered with higher doses after five years or even more [103]. It has been shown that 100% of the patients of reproductive age treated for Hodgkin's lymphoma with MOPP chemotherapy were azoospermic 14 months after the treatment [104,105]. The earliest sperm recovery has occurred 15 months after completion of the treatment, whereas some patients still presented an azoospermia 20 years after.…”
Section: Sperm Production and Recovery Periodmentioning
confidence: 99%
“…For instance, a return to normozoospermic levels was observed in 70% of men who received cumulative doses of cyclophosphamide under 7.5 g/m 2 , whereas only 10% recovered with higher doses after five years or even more [103]. It has been shown that 100% of the patients of reproductive age treated for Hodgkin's lymphoma with MOPP chemotherapy were azoospermic 14 months after the treatment [104,105]. The earliest sperm recovery has occurred 15 months after completion of the treatment, whereas some patients still presented an azoospermia 20 years after.…”
Section: Sperm Production and Recovery Periodmentioning
confidence: 99%
“…Alkylating agents such as procarbazine are highly toxic to the testis, causing depletion of the germinal epithelium and aplasia of germinal cells [44,45]. Most patients with HL, have poor semen quality following treatment and a low sperm density that is presented as oligospermia and permanent or transient azoospermia [46,47].…”
Section: Impact Of Anticancer Therapy On Fertility and Germ Cell Genomentioning
confidence: 99%
“…In patients with Hodgkin disease, fertility after treatment is also dependent upon the treatment regimen. Investigators have reported that the older MOPP treatment (mechlorethamine, vincristine, prednisone, and procarbazine) caused azoospermia in 100% (47 of 47 cases) of cases 1 year after treatment . In contrast, the newer ABVD regimen (doxorubicin, bleomycin, vinblastine, and dacarbazine) appears to be less toxic to spermatogenesis, as one study showed that 90% of men had no change in their sperm count 1 year after treatment …”
Section: Male Cancer Survivorshipmentioning
confidence: 99%